2020
DOI: 10.1016/j.aml.2019.106204
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary functions in the study of Stefan-like problems with variable thermal properties

Abstract: We address the existence and uniqueness of the so-called modified error function that arises in the study of phase-change problems with specific heat and thermal conductivity given by linear functions of the material temperature. This function is defined from a differential problem that depends on two parameters which are closely related with the slopes of the specific heat and the thermal conductivity. We identify conditions on these parameters which allow us to prove the existence of the modified error funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this note, a result for the existence and uniqueness of the solution to Pr. ( 1) is proved without any conditions on the parameters 𝛾 and 𝛿, which considerably extends the result in Ceretani et al 4 It is often very difficult, if not impossible, to find explicit solutions of such problems. However, the Adomian decomposition method (ADM) is the most important tool for finding solutions to this problem.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this note, a result for the existence and uniqueness of the solution to Pr. ( 1) is proved without any conditions on the parameters 𝛾 and 𝛿, which considerably extends the result in Ceretani et al 4 It is often very difficult, if not impossible, to find explicit solutions of such problems. However, the Adomian decomposition method (ADM) is the most important tool for finding solutions to this problem.…”
Section: Introductionsupporting
confidence: 75%
“…Also, explicit approximations solutions were provided in Bougoffa. 3 Recently, Ceretani et al 4 proved the existence and uniqueness of the solution of Pr. (1) under the following severely restrictive condition on 𝛿 and 𝛾 (Theorem 2.1 4 ):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the prescribed Gibbs-Thomson condition at the solid-molten interface leads to mathematical complexity of solving the Stefan problems analytically (Carslaw and Jaeger, 1959;Crank, 1984) so that asymptotic techniques, for example using the large Stefan number (Davis and Hill, 1982;Herrero and VelĂĄzquez, 1997; Kucera and Hill, 1986;McCue et al, 2008McCue et al, , 2009 and numerical methods (Crank, 1984;Meyer, 1973;Voller and Cross, 1981), are sought. The existence and uniqueness of certain functions related to phase-change problems are also studied (Ceretani et al, 2020). Moreover, the Gibbs-Thomson condition imposed on the moving boundary poses difficulty on using the Baiocchi transform so that one can not employ the enthalpy method (Meyer, 1973;Voller and Cross, 1981) to tackle the governing equations numerically (McCue et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…where δ and p are given non-negative constants, k 0 = k (θ f ) and c 0 = c (θ f ) are the reference thermal conductivity and the specific heat coefficients, respectively. Some other models involving temperature-dependent thermal conductivity can also be found in [3,4,11,13,23,24,26,27,36,38,40,41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%